2005
DOI: 10.1037/1528-3542.5.3.343
|View full text |Cite
|
Sign up to set email alerts
|

Negative cognitive styles, dysfunctional attitudes, and the remitted depression paradigm: A search for the elusive cognitive vulnerability to depression factor among remitted depressives.

Abstract: Results from studies using a behavioral high-risk design and approximations to it generally have corroborated the cognitive vulnerability hypothesis of depression, whereas results from remitted depression studies typically have not. Suspecting that design features of previously conducted remitted designs likely precluded them from detecting maladaptive cognitive patterns, the authors conducted a study featuring the remitted design that has been successful in studies of a biological vulnerability for depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 25 publications
(41 reference statements)
3
47
2
2
Order By: Relevance
“…Haeffel et al (2003) .93 3.64 .76 887 CSQ associated with lifetime history of clinically significant depression and the hopelessness depression subtype. Haeffel et al (2005) .93 3.62 .76 853 Remitted depressives have higher CSQ scores than never depressed participants. Haeffel et al (2007) CSQ interacted with self-reported life stress to predict depressive symptoms over a 5-week interval even after controlling for an implicit measure of cognitive vulnerability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Haeffel et al (2003) .93 3.64 .76 887 CSQ associated with lifetime history of clinically significant depression and the hopelessness depression subtype. Haeffel et al (2005) .93 3.62 .76 853 Remitted depressives have higher CSQ scores than never depressed participants. Haeffel et al (2007) CSQ interacted with self-reported life stress to predict depressive symptoms over a 5-week interval even after controlling for an implicit measure of cognitive vulnerability.…”
Section: Resultsmentioning
confidence: 99%
“…Further, preliminary research indicates that the CSQ, compared to the DAS, may be a more consistent predictor of depressive disorders (e.g., Haeffel et al, 2003), depressive and hypomanic symptoms (e.g., see Hankin et al, 2004 for exception), and level of daily negative cognitions . A number of studies have demonstrated incremental validity for the CSQ, as it is significantly associated with depressive symptoms and depressive disorders even after statistically controlling for the DAS (e.g., Haeffel et al, 2003;Haeffel et al, 2005). It should be noted, however, that a recent study by Oliver, Murphy, Ferland, & Ross, (2007) found that the DAS was associated more strongly with depressive symptoms than the CSQ.…”
Section: Comparing the Csq To Other Vulnerability Measuresmentioning
confidence: 99%
“…Haffel et al (2005) found that greater maladaptive cognitive patterns persisted with remitted depression compared with never-depressed controls, despite improvement in these cognitive patterns with depression treatment [105]. These authors argue, in their critical review of the literature on stability of trait vulnerability to depression, that to capture a baseline of vulnerable cognitive patterns for individuals after remission of their depression, studies would need to evaluate these individuals in their naturalistic setting, and these studies would need to be of a large enough size to be adequately powered from a statistical point of view.…”
Section: Interplay Of Temperament Cognitive Style and Stressmentioning
confidence: 99%
“…These authors argue, in their critical review of the literature on stability of trait vulnerability to depression, that to capture a baseline of vulnerable cognitive patterns for individuals after remission of their depression, studies would need to evaluate these individuals in their naturalistic setting, and these studies would need to be of a large enough size to be adequately powered from a statistical point of view. Currently, there are studies that confirm the hypothesis of complete resolution of a vulnerable cognitive style with depression treatment and studies that show a persistence of a maladaptive cognitive pattern, although much reduced from the pattern present with an unremitted or partially remitted depression [105]. The reader is referred to Haffel et al (2005) for a critical review of this topic.…”
Section: Interplay Of Temperament Cognitive Style and Stressmentioning
confidence: 99%
“…In times of increased stress, the triad of negative view of oneself, the environment, and the future is activated and characterizes the depressed individual's cognitive functioning. Studies support Beck's assumption that dysfunctional attitudes are linked to depression (for a review, see Haaga, Dyck, & Ernst, 1991), and a reduction in dysfunctional attitudes leads to fewer depressive symptoms when undergoing cognitive therapy (e.g., Quilty, McBride, & Bagby, 2008); yet, several studies have failed to detect the theoretically predicted elevated dysfunctional attitudes in remitted patients (e.g., Haeffel et al, 2005). This suggests that dysfunctional attitudes may only be evident once activated (Abela & Brozina, 2004).…”
mentioning
confidence: 99%